N-3 (OMEGA-3) FATTY ACIDS: EFFECTS ON BRAIN DOPAMINE SYSTEMS AND POTENTIAL ROLE IN THE ETIOLOGY AND TREATMENT OF NEUROPSYCHIATRIC DISORDERS - Healy-Stoffel, Michelle (CNS Neurol Disord Drug Targets, 2018)
A number of neuropsychiatric disorders, including Parkinson’s disease, schizophrenia, attention deficit hyperactivity disorder, and, to some extent, depression, involve dysregulation of the brain dopamine systems. The etiology of these diseases is multifactorial, involving genetic and environmental factors. Evidence suggests that inadequate levels of n-3 (omega-3) polyunsaturated fatty acids (PUFA) in the brain may represent a risk factor for these disorders. These fatty acids, which are derived from the diet, are a major component of neuronal membranes and are of particular importance in brain development and function. Low levels of n-3 PUFAs in the brain affect the brain dopamine systems and, when combined with appropriate genetic and other factors, increase the risk of developing these disorders and/or the severity of the disease. This article reviews the neurobiology of n-3 PUFAs and their effects on dopaminergic function. Clinical studies supporting their role in the etiologies of diseases involving the brain dopamine systems and the potential of n-3 PUFAs in the treatment of these disorders are discussed.